Interpretation of Protein Electrophoresis on Avian Samples - Arzour-Lakehal , N.; Boudebza, A. (International Journal of Poultry Science, 2021)
Background and Objective: Protein electrophoresis has been used in avian medicine as a diagnostic tool for many years, mainly in the diagnosis of inflammatory phenomena. The objective of this study was to compare protein profiles of normal plasma, hemolyzed plasma, normal serum and pathological serum of adult broiler chickens in order to provide a comprehensive review of plasma and serum protein electrophoresis in healthy and diseased chickens. Materials and Methods : The study involved 28 adult broilers from Isa 15 strain. Four mililitres of blood were drawn from the jugular vein. Half of the blood was collected in heparinized tubes and immediately separated by centrifugation. The rest of the whole blood was collected in dry tubes, incubated at 30°C for 2 h and then centrifugated. Hemolyzed plasmas were previously frozen-thawed 3 times to induce hemolysis and subsequently centrifuged. Pathological sera of chickens with New Castle disease confirmed with the hemagglutination-inhibition test. Agarose gel electrophoresis of freezed undiluted plasma and serum was used and the biuret method for total protein concentration was used for all samples. Results: Electrophoresis revealed the following protein fractions in plasma and serum samples: albumin, α1-globulins, α2-globulins, pre β-globulins, β1-globulins, β2-globulins and γ-globulins. The result is expressed by a curve with 7 peaks. Densitometric quantification of plasma protein fractions revealed a very significant increase in total proteins, β1-globulins fraction, γ-globulins fraction and a significant increase in β2-globulins fraction. The ratio A/G was significantly lower in plasma when compared to serum samples. Hemolysis resulted in a significant increase in plasma α2-globulins fraction and pre β-globulins fraction. Densitometric quantification of serum protein fractions from diseased chickens revealed a significant decrease in albumin and A/G ratio and a very significant increase in total proteins, α1-globulins, all proteins of beta and gamma fraction. Conclusion: This study has shown differences between the electrophoretic patterns of plasma, serum, hemolyzed plasma and abnormal values for protein electrophoresis in birds with New Castle disease were reported. Therefore, the results must be interpreted according to the nature of the sample and the condition of the animal. Protein electrophoresis is the most reliable assessment of avian protein profiles in healthy and diseased patients.